Effect of Infection on Nutritional Status of Infants in a Cohort Study of Vitamin a in Western Kenya (P10-121-19). (13th June 2019) - Grant, Frederick; Wanjala, Rose; Low, Jan; Levin, Carol; Coke, Donald; Okuku, Haile; Ackatia-Armah, Robert; Girard, Amy Webb
Abstract: Objectives: Infection is associated with impaired nutritional status especially of infants under 5 years old. We assessed the impact of infection indicated by both the acute phase proteins (APP), C-reactive protein (CRP) and α-1-acid glycoprotein (AGP), and as reported by maternal recall on the nutritional status of infants. Methods: 505 pregnant women were enrolled into a nested longitudinal cohort study of vitamin A. Data analysis was restricted to infant data at 9-months ( n = 385 mother-infant dyads) postpartum. Incidence and severity of respiratory infection and diarrhea over the previous 14 days were assessed by maternal recall; information on infant/child feeding practices were also collected. Infant weight, recumbent length and heel-prick capillary blood collection were taken at 9-months postpartum. Indicators of VA status [(retinol binding protein (RBP)], iron status (Hb, ferritin) and subclinical inflammation APP, CRP and AGP, were determined. Subclinical inflammation was defined as CRP >5 mg/L and/or AGP >1 g/L. Impacts of infection on infant nutritional status were estimated with multivariable logistic regression models adjusted for clustering and differences at enrollment. Results: Infection prevalence, based on elevated CRP and AGP levels, was 36.7%. For diarrhea reported symptoms, 42.4% of infants at 9-months had no indication of infection as indicated by CRP and AGP; whilst for acute respiratory reported symptoms, 42.6% had no indication of infection. There was a weak but significant positive association with infection among VA deficient (RBP <0.83 µmol/L) infants based on maternal reported symptoms but not with iron deficiency (ferritin <12 µg/L). The odds of having infection, based on raised CRP and AGP, in underweight infants was 3.7 times higher (OR: 3.7; P = 0.019). Infants with iron deficiency were less likely (OR: 0.40; P = 0.001) to have infection based on CRP and AGP, whilst infants with VA deficiency were 5 times more likely (OR: 5.06; P = 0.0001) to have infection. Conclusions: Acute phase proteins are more useful in defining infection in a population compared to reported symptoms of illness. Not controlling for inflammation in a population while assessing nutritional status might result in inaccurate prevalence estimation. Funding Sources: Supported by the Bill &Melinda Gates Foundation (OPP53344).